Plano educacional individualizado: aplicativo de uso colaborativo na elaboração do PEI para um aluno autista - Almeida, Fernanda Correia de Lima (Universidade Federal do Tocantins, 2023)
Given the growing demand of autistic students enrolled in the regular school network, the object of research resulting in this dissertation was the form of educational planning directed to this public. In this sense, the proposal took place in the elaboration of the Individualized Educational Plan – PEI (hereinafter), for autistic students enrolled in the regular education network in a school, in the city of Balsas, southern region of Maranhão. This research aimed to understand how a collaborative pedagogical practice is developed between teachers of regular education and special education in the elaboration of the Individualized Teaching Plan - PEI for the autistic student. The specific objectives were to reflect on the legal bases of Special and Inclusive Education and its contributions in the elaboration of a PEI; to present pedagogical planning as an intentional tool in the schooling of students with disabilities; accompany the teachers of regular education and special education in the elaboration of the Individualized Teaching Plan for the autistic student and propose an application to guide the elaboration of the individualized educational plan for the target public student of special education. The methodology used was qualitative based on the assumptions of action research and also included documentary research and structured interviews. As a theoretical framework we used the historical-cultural perspective of Vygotsky (1994, 2007, 2010) articulated with the concept of intellectual disability presented in his writings. As an educational product of the research, an application called PEI- DIGITAL was elaborated - an app that can be used by the regular schools of the municipal network, as a facilitating mechanism for the elaboration of the Individualized Educational Plan for students with disabilities. This application will be for internal use of the school, with mutual access between the teachers involved and that can be filled collectively after the definitions of the objectives, goals, strategies and necessary curricular adaptations. Finally, it was evidenced in the research, the importance of the elaboration of the PEI through the collaborative work between the teachers of the regular education and special education.